2020
DOI: 10.1111/1751-2980.12867
|View full text |Cite
|
Sign up to set email alerts
|

The use of combination biological or small molecule therapy in inflammatory bowel disease: A retrospective cohort study

Abstract: ObjectiveThere are limited data on using more than one biologic or small molecule drug combined to treat patients with inflammatory bowel disease. The aim of our study was to determine the effectiveness and safety of combination biologic use in inflammatory bowel disease.MethodsWe identified patients with Crohn's disease or ulcerative colitis who received treatment with a combination of two biologics or a biologic and a small molecule drug from 2015 to 2019 for persistent disease activity or concomitant rheuma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 19 publications
1
56
0
2
Order By: Relevance
“…While there have been a number of recent reports using a combination of two biologics or a small molecule and a biologic in refractory IBD cases 5,6,8,[22][23][24] , most of these reports have been limited to DBT with only two case series and a case report reporting on TBT. 5,25,26 Glassner et al reported the overall effectiveness and safety of various combinatorial therapies in a cohort of 50 patients. 5 Although, they reported the rate of AEs among the 20 patients on TBT in their cohort, the effectiveness in this subgroup was not separately reported.…”
Section: Discussionmentioning
confidence: 99%
“…While there have been a number of recent reports using a combination of two biologics or a small molecule and a biologic in refractory IBD cases 5,6,8,[22][23][24] , most of these reports have been limited to DBT with only two case series and a case report reporting on TBT. 5,25,26 Glassner et al reported the overall effectiveness and safety of various combinatorial therapies in a cohort of 50 patients. 5 Although, they reported the rate of AEs among the 20 patients on TBT in their cohort, the effectiveness in this subgroup was not separately reported.…”
Section: Discussionmentioning
confidence: 99%
“…While there have been a number of recent reports using a combination of two biologics or a small molecule and a biologic in refractory IBD cases 5,6,8,[22][23][24] , most of these reports have been limited to DBT with only two case series and a case report reporting on TBT. 5,25,26 Glassner et al reported the overall effectiveness and safety of various combinatorial therapies in a cohort of 50 patients. 5 Although, they reported the rate of AEs among the 20 patients on TBT in their cohort, the effectiveness in this subgroup was not separately reported.…”
Section: Discussionmentioning
confidence: 99%
“…5,25,26 Glassner et al reported the overall effectiveness and safety of various combinatorial therapies in a cohort of 50 patients. 5 Although, they reported the rate of AEs among the 20 patients on TBT in their cohort, the effectiveness in this subgroup was not separately reported. Clark-Snustad et al reported the rate of AEs in 18 patients on TBT for refractory CD without separately reporting the effectiveness in this cohort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Janus kinase inhibitors in UC targeting multiple inflammatory pathways may offer advantages over monoclonal antibodies targeting specific cytokines; 2 however, studies regarding the safety and effectiveness of combination biologic and small molecule therapies in UC are limited. 3,4 We herein describe the use of tofacitinib in combination with infliximab for the management of UC.…”
Section: Tofacitinib Is Safe and Effective When Used In Combination Wmentioning
confidence: 99%